PENGARUH POSITIVE EMOTION TERHADAP IMPULSE BUYING DENGAN PRODUCT INVOLVEMENT SEBAGAI VARIABEL MODERASI PADA PEMBELIAN PRODUK FASHION DI SHOPEE - Suwanti, Suwanti; Hadi, Abdul; Haris, Abdul (Widya Dharma Journal of Business - WIJoB, 2023)
The aim of the research is 1) to find out analyze the effect of positive emotion on impulse buying when purchasing fashion products at Shopee. 2) to find out and analyze whether product involvement strengthens or weakens the positive emotion relationship to impulse buying when purchasing fashion products at Shopee. Data collection thechniques with questionnaires, interviews, and observation. The sample in this study were 125 students from Widya Dharma University Klaten. The variables in this study are the independent variable: Positive Emotion (X), the dependent variable: Impulse Buying (Y), and the moderating variable: Product Involvement (Z). data analysis techniques used simple linier regression analysis and Moderated Regression Analysis (MRA) with the help of the SPSS version 25 program. From the results of the t test it is known that, positive emotion with t count 5,546 > t table 1,1979 and a significance value of 0,037 < 0,05 then there is a positive and partially significant effect of positive emotion on impulse buying, moderation regression test with t count 2,109 > t table 1,979 and a significance value of 0,037 < 0,05. so product involvement is able to moderate the effect of positive emotion on impulse buying Keywords: Positive Emotion, Impulse Buying, and Product Involvement